2009
DOI: 10.2967/jnumed.109.062687
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of 18F-Labeled 6-Fluoro-6-Deoxy-d-Glucose by Skeletal Muscle Is Responsive to Insulin Stimulation

Abstract: We are developing a methodology for the noninvasive imaging of glucose transport in vivo with PET and 18F-labeled 6-fluoro-6-deoxy-d-glucose (18F-6FDG), a tracer that is transported but not phosphorylated. To validate the method, we evaluated the biodistribution of 18F-6FDG to test whether it is consistent with the known properties of glucose transport, particularly with regard to insulin stimulation of glucose transport. Methods Under glucose clamp conditions, rats were imaged at the baseline and under condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 29 publications
0
25
0
Order By: Relevance
“…20) and that of phosphorylation by hexokinase K H g is set to 0.13 mM. 21 As the Michaelis constant for 6FDG transport (K G 6FDG ) has not yet been determined, we made a preliminary estimate of 10 mM based on published 22 and unpublished experimental data. Also, we assume that the Michaelis constant of 2FDG transport (K G 2FDG ) is 8 mM based on unpublished experimental data and that of phosphorylation by hexokinase K H 2FDG equals 0.17 mM.…”
Section: Iic Classic Simulations Of Pet Data In Rat Skeletal Musclementioning
confidence: 99%
See 1 more Smart Citation
“…20) and that of phosphorylation by hexokinase K H g is set to 0.13 mM. 21 As the Michaelis constant for 6FDG transport (K G 6FDG ) has not yet been determined, we made a preliminary estimate of 10 mM based on published 22 and unpublished experimental data. Also, we assume that the Michaelis constant of 2FDG transport (K G 2FDG ) is 8 mM based on unpublished experimental data and that of phosphorylation by hexokinase K H 2FDG equals 0.17 mM.…”
Section: Iic Classic Simulations Of Pet Data In Rat Skeletal Musclementioning
confidence: 99%
“…21 For both basal and EH conditions, plasma glucose concentration (P g ) was set to 6 mM, consistent with our prior experimental data in the rat. 22 IS g was specified as 85% of P g (¼5.1 mM) and 50% of P g (¼3 mM) for basal and EH conditions, respectively. 19 From the skeletal muscle blood flow in rats, 23 we assume k 1 ¼ 0.04 min À1 for basal conditions.…”
Section: Iic Classic Simulations Of Pet Data In Rat Skeletal Musclementioning
confidence: 99%
“…[1][2][3]5 We also developed a new model for the quantitative analysis of 6-[ 18 F]FDG concentration time-courses measured using PET imaging and confirmed that the model predicts that insulin and hyperglycemia lead to increased glucose transport with insulin causing an increase and hyperglycemia causing a decrease in intracellular concentrations of the tracer. 4 Taken together, these studies demonstrate the potential for using 6-[ 18 F]FDG to measure in vivo glucose transport at the tissue level and in a minimally invasive way.…”
Section: Introductionmentioning
confidence: 99%
“…18 F]FDG preparation 6-[ 18 F]FDG was synthesized from the 3,5-O-benzylidene-6-deoxy-1,2-O-isopropylidene-6-(4 -methylbenzene)sulfonyl oxy-alpha-D-glucofuranose precursor using modification of a previously described method 1,6 and using a GE Healthcare TRACERlab FX F-N automated synthesis module. The resulting product was purified using combined C-18 and neutral Alumina Sep-Paks (Waters Corporation) and was formulated in sterile water for intravenous injection.…”
Section: A 6-[mentioning
confidence: 99%
See 1 more Smart Citation